Dexmedetomidine modulates mitochondrial dynamics to protect against endotoxin-induced lung injury via the protein kinase C-ɑ/haem oxygenase-1 signalling pathway. (17th February 2022) - Song, Kai; Shi, Jia; Zhan, Lina; Gao, Qiaoying; Yang, Jing; Dong, Shuan; Zhang, Yuan; Yu, Jianbo
Abstract: Background: Endotoxin-induced acute lung injury (ALI) has a high mortality rate, and there are limited effective treatment options available. The aim of the present study was to identify if dexmedetomidine could regulate mitochondrial fusion and fission through the protein kinase C (PKC)-α/haem oxygenase (HO)-1 pathway to protect against endotoxin-induced ALI. Materials and methods: Dexmedetomidine was administered by intraperitoneal injection once daily for three days prior to induction of lung injury to mice. Mice in the PKC-α inhibitor group received dexmedetomidine by intraperitoneal injection 1 h after each chelerythrine injection, and lipopolysaccharide was injected 1 h after the last dose of dexmedetomidine. The lung wet/dry weight ratio, oxidative stress, inflammatory response, and expression levels of PKC-α, Nrf2, HO-1, Mfn1, Mfn2, OPA1, Drp1, and Fis1 were determined. Results: Dexmedetomidine administration attenuated lung oxidative stress, decreased inflammatory cytokines secretion, and downregulated the expression levels of Drp1 and Fis1. Moreover, dexmedetomidine increased levels of Mfn1, Mfn2, and OPA1, and alleviated endotoxin-induced lung injury. Administration of chelerythrine partially reversed the pneumoprotective effects of dexmedetomidine. Conclusions: Dexmedetomidine may activate the PKC-ɑ/HO-1 pathway to increase the expression of Mfn1, Mfn2, and OPA1, while decreasing Drp1 and Fis1 expression, thereby reduce endotoxin-induced acute lung injury.